(untitled) (Bangladesh Heart Journal, 2018)
A 2 years old boy presented to us with a history of repeated respiratory tract infections and bluish discoloration of tongue, lips and figure tips for last 18 months. Echocardiography and Computed tomography (CT) angiogram revealed total anomalous pulmonary venous connection (TAPVC) mixed type (supracardiac and cardiac);all pulmonary veins drain into a common chamber behind left atrium (LA) and left lower pulmonary vein (LUPV) drains to vertical vein and common chamber both.The patient underwent rerouting of pulmonary veins and vertical vein ligation above the drainage of LUPV. Bangladesh Heart Journal 2018; 33(2) : 138-140